Exploring the Issues of Counseling Teachers with Non-Guidance and Counseling Backgrounds from the Perspective of the Professional Code of Ethics - Diandra Sukmawati; Isna Zahuratul Fairuz Fairuz; Naila Salsabila Munigar Munigar; Najwa Dhiyaul Haq Haq; Silva Savitri Savitri; Zaskia Hilmah Salamah El Mahmudiyah El Mahmudiyah; Nadia Aulia Nadhirah (Ma'soem University, 2024)
Guidance and counseling teachers with Non guidance and counseling backgrounds are still an issue that often occurs in education in Indonesia. This is caused by the limited number of guidance and counseling teachers in Indonesia. Therefore, the aim of this research is to explore and find out more deeply about guidance and counseling teachers with non-counseling backgrounds from a guidance and counseling perspective. This research uses descriptive qualitative methods to explain in more detail the data from interviews with both guidance and counseling teachers and guidance and counseling teachers with Non guidance and counseling backgrounds. The results obtained are that guidance and counseling teachers with Non guidance and counseling backgrounds do not really understand and delve into the code of ethics for guidance and counseling. However, in practice, guidance and counseling teachers who come from the psychology department (non-counseling) have adequate understanding regarding counseling, so their presence helps reduce the workload of guidance and counseling teachers. Keywords: Code of Ethics; professional ethics; Non guidance and counseling guidance and counseling teachers.